Pengaruh Pembelajaran PPKn Berbasis Discovery Learning terhadap Hasil Belajar pada Siswa Kelas X IPA Batara Gowa - Rismawati Rismawati; Mardiana Mardiana; Syamsir Syamsir (Universitas of Muhammadiyah Makassar, 2019)
The problems in this study are (1) What is the PPKn Learning Process in Gowa Batara High School? and (2) Is there any influence of Discovery Learning-Based PPKn learning on learning outcomes in high school students of class X IPA Batara Gowa ?. This study aims at (1) to find out the PPKn learning process in class X of Batara Gowa High School Science and (2) to determine the effect of PPKn learning based on Discovery Learning on learning outcomes of class X IPA SMA Batara Gowa students. The research method used in this study is an experimental method with a form of research, which is a quasi-experimental (quasi experimental design) and a research design that is used is a technique of collecting data in the form of observation and learning outcomes. The data analysis technique used is the technique of analyzing the data of test results and questionnaires. The results of this study indicate that the Discovery Learning learning model can be improved on the learning outcomes of students in Batara Gowa High School Science X class based on the calculation of pretest and posttest test data analysis using t count X, Y, d, and d2, namely the total X value of 1.130 % and the average value of 51.36%. While the value of Y is 1.560%, with an average value of 70.90%. For the value of d with the amount of 420 with an average value of 19.09 and for the value of d2 with the number 12,200% with an average value of 554.54%. So there is an influence on the differences in the average learning outcomes of students who use the Discovery Learning learning model with the average student learning outcomes.Keywords : Learning, Discovery Learning and Student Learning Outcomes